Polymers and Kinetic Resolutions: The Insolubility of It All. Issue 5 (5th February 2016) - Clark, Robert W.; Akhani, Ravish K.; Wiskur, Sheryl L.
Abstract: Kinetic resolution is a powerful technique to obtain enantioenriched compounds. A major drawback to conventional kinetic resolutions is that the final purification step to isolate the stereoenriched compounds usually employs chromatography, which is costly and difficult to perform on an industrial scale. Recent advances have demonstrated the applicability of polymer supports as a means of separating enantiomerically enriched starting materials from products in kinetic resolutions by having one enantiomer attached to the polymer and the other in solution. Herein, several approaches are reviewed in which either homogenous or heterogeneous macromolecules are employed to facilitate a chromatography‐free isolation of stereoenriched compounds. Kinetic resolutions employing enzymatic, transition‐metal, or small‐molecule‐catalyzed reactions by using polymeric materials will be discussed. Abstract : Enantiomer separation : The chromatography‐free separation of enantiomers through the use of polymers in kinetic resolutions is highlighted. The three methods discussed all result in one enantiomer free in solution and the other enantiomer as part of the polymer that can be removed through filtration.